RANCANG BANGUN SISTEM E-LEARNING BERBASIS WEB (STUDI KASUS MA AN NAWAWIYAH) - Setiawati, Siska (Universitas Majalengka, 2021)
Each educational unit continues to strive for the best learning methods for their students, including MA An Nawawiyah. There needs to be an application that supports communication between students and teachers in delivering learning materials and assignments. Through the e-learning application it is felt that it will make it easier for students and teachers to continue to carry out learning activities even though it is a distance (in a network. With the Rapid Application Development (RAD) system design method, this study was made with the aim of: (1) knowing the process of e -learning at MA An Nawawiyah web-based and (2) knowing the implementation of the e-learning system design in MA An Nawawiyah web-based.